The role of hsp 70 in the implementation of neuroprotective effect of selective estrogen receptor modulator (serm) in deprivation of the system`s level of restored glutathione in vitro6 - Belenichev, I. F.; Egorov, A. A.; Zaporozhchenko, E.; Ryzhenko, O.; Бєленічев, Ігор Федорович; Єгоров, Артем Анатолійович; Запорожченко, Є.; Риженко, О. (Запорізький державний медичний університет, 2018)
The aim of the research: to determine the value of the heat shock protein HSP 70 in the implementation of the mechanism of neuroprotective actions of selective estrogen receptor modulator (SERM) – (Z)-2-[4-(1,2-diphenyl-1-butenil)fenoxy]-N, N-dimethilaethanamin citrate. The objective of this study was to estimate the influence of SERM on the expression of HSP70, the activity of the thiol-disulfide system of neurons and mitochondria development of neuronal apoptosis in vitro, with a deficit of restored glutathione.
Keywords: тези доповідей